Kualitas Pelayanan Izin Cerai Aparatur Sipil Negara di Badan Kepegawaian Daerah Provinsi Jawa Timur - Indrawati, Tri Mei; M, Meirinawati; Fanida, Eva Hany; Oktariyanda, Trenda Aktiva (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Divorce permit services for civil servants (ASN) are part of personnel administration services that are highly sensitive because they relate to personal matters, ethics, and civil service discipline. Therefore, the quality of divorce permit services is an important aspect in maintaining bureaucratic professionalism and civil servants' trust in government institutions. This study aims to analyze the quality of divorce permit services for ASN at the Regional Civil Service Agency (BKD) of East Java Province using Kotler and Keller's service quality theory, which includes the dimensions of physical evidence, reliability, responsiveness, assurance, and empathy. This study uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The results show that the quality of divorce permit services for ASN at the BKD of East Java Province is generally in the good category. The dimensions of assurance and empathy are the most prominent aspects, as demonstrated by the professional attitude of officers, consistency of information, protection of privacy, and personal attention to ASN as service users. However, the physical evidence and reliability dimensions still need improvement, particularly in relation to service facility limitations and the timeliness of administrative processes. This study recommends improving service infrastructure, optimizing information delivery, and strengthening internal coordination to continuously improve the quality of civil servant divorce permit services.